Favourable modulation of osteoblast cellular activity on Cu-containing austenitic stainless steel and comparison with the Cu-free counterpart. (6th June 2020) - Gong, N.; Misra, R.D.K.
ABSTRACT: In the present study, we describe the favorable modulation of osteoblast functions on Cu-containing austenitic stainless steel in comparison to the Cu-free steel. A series of biological experiments were conducted to understand the determining role of Cu in stainless steel on cellular activity. The study clearly demonstrated that cell attachment, proliferation, and cell-material interactions were significantly enhanced in the presence of Cu. The % area covered by cells increased from 13.4% to 17.8% on Cu-free steel and 17.7% to 25.2% on Cu-containing steel after 2 h and 24 h of incubation, respectively. Similarly, the cell density increased from 3845 cells/cm2 to 5481 cells/cm2 on Cu-free steel and 4990 cells/cm2 to 8590 cells/cm2 on Cu-containing steel after 2 h and 24 h of incubation, respectively. It is underscored that copper can be added to biomedical alloys from the perspective of cellular functions.